Validation of DWI in assessment of radiotreated bone metastases in elderly patients. (September 2016) - Reginelli, Alfonso; Silvestro, Giustino; Fontanella, Giovanni; Sangiovanni, Angelo; Conte, Mario; Nuzzo, Iolanda; Calvanese, Mariagrazia; Traettino, Marianna; Ferraioli, Piera; Grassi, Roberta; Manzo, Roberto; Cappabianca, Salvatore
Abstract: Bone metastases are commonly observed in oncologic patients with advanced disease. These metastases are considered the main cause of neoplastic pain, with more than half of oncologic patients experiencing neoplastic pain during the course of the disease due to bone involvement. Lung, breast, and prostate cancers are the primary causes of bone metastases. Magnetic resonance imaging (MRI), especially diffusion weighted imaging (DWI) sequences, is the focus of our research, as it has been proven to be an optimal predictive index to assess the radiation treatment in many patients. We included patients treated with standard fractioning of radiation therapy. First, we examined the irradiated lesions with the MRI-DWI technique, before treatment and 30 and 60 days after its completion. Then we combined the MRI results and clinical parameters in a table with a predictive score for the quality of life in patients with bone metastases. This was a significant predictor of the efficacy of radiation treatment, from both clinical and psychological points of view, as it can allow an early assessment of the response to RT and therefore better scheduling of the next therapeutic steps to be performed. The table of the score we proposed helped guide patient monitoring, enabling us to undertake, where possible, follow-up with therapeutic strategies tailored to each patient's needs.